ANALISIS PENGARUH KEPEMIMPINAN PELAYAN, PENGEMBANGAN KARIR DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA (STUDI KASUS PADA PERANGKAT DESA SE-KECAMATAN GEMUH KABUPATEN KENDAL) - Tri Sumiyanti; Jati Widya Iswara; Santoso Santoso (CV. ALIM'SPUBLISHING, 2025)
The purpose of this study was to determine the effect of servant leadership on the performance of Village Apparatus in Gemuh District, Kendal Regency. To determine the effect of career development on the performance of Village Apparatus in Gemuh District, Kendal Regency. To determine the effect of organizational commitment on the performance of Village Apparatus in Gemuh District, Kendal Regency. The population in this study was Village Apparatus in Gemuh District, Kendal Regency. Sampling using accidental sampling technique, namely determining the number of samples by taking randomly by giving equal opportunity to the existing population to be sampled. The number of samples obtained was 82 respondents. The data used were primary data using questionnaires. Data analysis using multiple linear regression analysis. Based on the results of the study, it can be concluded that servant leadership has a positive and significant effect on the performance of Village Apparatus in Gemuh District, Kendal Regency. Career development has a positive and significant effect on the performance of Village Apparatus in Gemuh District, Kendal Regency. Organizational commitment has a positive and significant effect on the performance of Village Apparatus in Gemuh District, Kendal Regency.